Evaluation of the Examination of Public Appraisers and Public Appraisal Service Offices at the Center for Financial Profession Development - Marbun, Ganda Tua Hasiholan; Fitriany, Fitriany (E-Jurnal Akuntansi, 2024)
The study aims to evaluate the implementation of the examination of Public Appraisers (PP) and Public Appraisal Service Offices (KJPP) by the Financial Profession Development Center (PPPK) based on factors of top management support, human resources, and Examination Guidelines. The background of the study was the increase in the number of examination findings and complaints against PP and KJPP which showed non-compliance of PP and KJPP with laws and regulations, codes of ethics, and professional standards, so that it could give rise to legal cases. The method in the study used a descriptive qualitative approach through a case study of an evaluation model of data on PPPK and interviews with PPPK employees including the examination team (members, chairs, and coordinators). The results of the study showed that the implementation of the examination of PP and KJPP at PPPK had been carried out based on risk and in accordance with regulations and Examination Guidelines. In order to improve, an examination blueprint is needed, increased firmness in imposing sanctions, motivation for the examination team to pass the certification exam, and the addition of provisions and formats for the examination team's work papers in the Examination Guidelines. Keywords: Examination; Public Appraiser; Public Appraisal Service Office; Center for Development of Financial Profession.